Combination of a monofocal and one type of extended depth-of-focus (zonal refractive) intraocular lens (COMEDI) in bilateral cataract surgery protocol: a monocentric, randomised, parallel group trial in cataract surgery - Sorcha Ní Dhubhghaill; Silke Oellerich; Wilfried Cools; Heleen Delbeke; Iva Krolo; Karolien Termote; Roger Van Schoor (BMJ Open Ophthalmology)
Introduction Modern intraocular lens (IOL) designs for cataract treatment can be broadly classified into three focal range categories; monofocal, extended depth-of-focus (EDOF) and multifocal IOLs.Monofocal IOLs allow spectacle independence for one focus, typically distance. In contrast, EDOF IOLs provide a greater range of vision, extending spectacle independence to intermediate distance, while multifocal IOLs enable spectacle independence at all distances with the drawback of positive dysphotopsias and reduced contrast perception.EDOF lenses are an attractive compromise with fewer dysphotopic side effects than multifocals. The purpose of this study is to assess whether implanting an EDOF IOL in the second eye of a patient who received a monofocal IOL in the first eye can improve spectacle independence while maintaining the same optical quality as bilateral monofocal IOL implantation.Methods and analysis This study compares combined monofocal and EDOF IOL implantation versus bilateral monofocal IOL implantation in terms of clinical and patient-reported outcomes in a monocentric, randomised, patient-masked and assessor-masked, parallel group trial in 88 bilateral cataract patients. The primary outcome measure is binocular photopic distance corrected intermediate visual acuity. The secondary outcome measures include (un)corrected distance and near visual acuity, reading speed at intermediate distance, quality of visual function assessments, patient-reported spectacle independence, contrast sensitivity, aberrometry, stereopsis and straylight measurement at the 3-month follow-up.Ethics and dissemination The protocol was approved by the ethical committee of the University Hospital of Brussels (BUN 23219_EDOF).Trial registration number NCT06002399